ANALISIS MODEL PENGEMBANGAN INFRASTRUKTUR JARINGAN KOMPUTER PADA UNIVERSITAS TEKNOLOGI SUMBAWA SEBAGAI INOVASI MENGGUNAKAN METODE PPDIOO - WIDIARTA, I MADE; Esabella, Shinta; Widiantara, Putu Widiantara (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2020)
The purpose of this research is to develop computer network infrastructure managementat the Sumbawa University of Technology. The research begins by analyzingcomputer network infrastructure that is running, then donedevelopment of computer network infrastructure management to improve performancemanagement of data and information exchange. The research method used isPPDIOO (Prepare, Plan, Design, Implement, Operate, and Optimize) which isnetwork design method from Cisco as a network service life cyclein supporting the development of computer networks. At the Prepare stage, it is carried outanalysis of the existing infrastructure using the existing Net Toolsavailable on Android Smartphones to analyze Wifi availability anduse Host Tracker to test server stability. Furthermore, at the Plan stageand the design is carried out to develop the existing infrastructure. Results of the Implement stagewill be tested again to ensure the network infrastructure is operationaloptimal. The results showed that the area that is not covered by WiFi(Blank Spot) has decreased. The availability of the server also has Up Timeabove 99.9%. So it can be concluded in this study, that withusing the new infrastructure design is able to provide availabilitya more optimal network to support the Smart Campus program at the UniversitySumbawa technology.